Technology foresight in communications regulation - Suppapol Jaroonvanichkul (International Telecommunications Society (ITS), 2023)
Technologies are changing rapidly in the communications industry, posing challenges for communications regulators. Regulators need to anticipate and prepare for future technological changes to make informed decisions on regulatory actions that foster innovation and protect consumers. This paper examines the application of technology foresight in communications regulation, based on a literature review. It discusses the importance of technology foresight in addressing the pacing problem, managing environmental uncertainty, and supporting the roles of communications regulators. The paper discusses a framework for conducting technology foresight in communications regulation, primarily based on "Framework Foresight." Additionally, it explores foresight methods and the institutionalization of foresight within organizations. By utilizing technology foresight, regulators can identify emerging technologies, assess their potential impacts, and develop appropriate regulatory responses.
Keywords: 330; Foresight; Regulation; Technological Change